The Cultural Universe of the Nuaulu Tribe: A Testament to Commitment to Unity, Tradition, and Mutual Trust - Segara, I Nyoman Yoga; Budiasa, I Made; Harsana, I Ketut Gede; Lamopia, I Wayan Gede; Jayanti, I Gusti Ngurah (Journal of Ethnic and Cultural Studies, 2023)
Engaging in research within the interdisciplinary realms of ethics and cultural studies is immensely important. This study delves into the social institutions of the Nuaulu people, an indigenous community inhabiting the Seram Island of Indonesia. The analysis focuses on Mataruma, Traditional Rulers, and Traditional Houses, shedding light on their roles, significance, and implications for the community. The research draws on a combination of interviews and references to prior studies to construct a comprehensive narrative about these social institutions. The Mataruma system, characterized by gender equity and shared responsibilities, stands as a testament to the Nuaulu’s commitment to unity, tradition, and mutual trust. Traditional Rulers, the intermediaries between the human world and the realm of ancestors, play a pivotal role in preserving religious practices, reinforcing collective faith, and maintaining cultural integrity. The traditional houses, constructed from natural materials, serve as sacred spaces for rituals, symbolizing the connection between the living and the spiritual world. This in-depth analysis thoroughly explores the Nuaulu social institutions and their enduring influence on the preservation and enrichment of their culture. This study enriches our comprehension of the Nuaulu tribe’s distinctive cultural heritage and also underscores the significance of cultural preservation in the face of evolving religious identities, contributing substantially to the broader discourse in the fields of ethics and cultural studies.